2013
DOI: 10.1371/journal.pcbi.1003088
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing MHC-I Binding Peptides and Their Limits of Variation

Abstract: Designed peptides that bind to major histocompatibility protein I (MHC-I) allomorphs bear the promise of representing epitopes that stimulate a desired immune response. A rigorous bioinformatical exploration of sequence patterns hidden in peptides that bind to the mouse MHC-I allomorph H-2Kb is presented. We exemplify and validate these motif findings by systematically dissecting the epitope SIINFEKL and analyzing the resulting fragments for their binding potential to H-2Kb in a thermal denaturation assay. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 57 publications
0
34
0
4
Order By: Relevance
“…Considerable efforts have been dedicated to the development of accurate methods for the prediction of peptide binding to MHC molecules, applying many different approaches including similarity matrices (Kim et al, 2009), linear regression (Wang et al, 2015) and artificial neural networks (Hoof et al, 2009;Koch et al, 2013;Kuksa et al, 2015), among others. Of these methods, NetMHC (Nielsen et al, 2003) has been shown in several benchmark studies to be a state-of-the-art predictor for peptide-MHC binding affinity (Lundegaard et al, 2008;Peters et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been dedicated to the development of accurate methods for the prediction of peptide binding to MHC molecules, applying many different approaches including similarity matrices (Kim et al, 2009), linear regression (Wang et al, 2015) and artificial neural networks (Hoof et al, 2009;Koch et al, 2013;Kuksa et al, 2015), among others. Of these methods, NetMHC (Nielsen et al, 2003) has been shown in several benchmark studies to be a state-of-the-art predictor for peptide-MHC binding affinity (Lundegaard et al, 2008;Peters et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high sensitivity of modern fluorimeters, DSF is well suited to low volume, rapid measurements on multiple samples. DSF has found numerous uses in characterizing protein stability and ligand binding, and has been recently used to assess the binding of peptides to class I MHC proteins (Gras et al, 2012; Koch et al, 2013a; Koch et al, 2013b; Hassan et al, 2015), as well as the impact of peptides and other molecules binding to class II proteins (GĂŒnther et al, 2010; Rupp et al, 2011; Clayton et al, 2014), including HLA-DM (Álvaro-Benito et al, 2015). Although early applications of DSF required customized fluorimeters, the technique is easily adaptable to fluorescence-equipped RT-PCR instruments common to many molecular biology laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al proposed both a colored and non-colored bipartite networks [Luo et al, 2016]. Shallow and high-order artificial neural networks were proposed from various labs [Hoof et al, 2009, Koch et al, 2013, Kuksa, 2015, Nielsen et al, 2003. Of these approaches, NetMHC/NetMHCpan have been shown to achieve state-of-the-art for MHCpeptide binding prediction [Nielsen et al, 2016, Trolle et al, 2015.…”
Section: Introductionmentioning
confidence: 99%